Uang Kartal Dalam Pendekatan Hukum Ekonomi Dan Hukum Ekonomi Syariah - Ahmad Yani, Encep; Widjajanto, Haswar (ARBITRASE: Journal of Economics and Accounting, 2023)
The rapid progress of science and technology in today's digital era has brought revolutionary changes in transactions, no need to queue up to make a passbook, wait for an ATM card to be issued, now all of that is no longer needed, just install the application, top up the balance already can directly transact. This study uses a descriptive analysis method, which is a method that functions to describe or give an overview of the object under study through data or samples that have been collected as they are without conducting analysis and making general conclusions. The results of the study show that the four electronic money products above (Sakuku BCA, Link Aja, OVO and Go Pay), represent their presence in Indonesia that need attention from the regulatory side and also need attention from the aspect of shari'ah studies, considering the users of money products The majority of these electronics are Muslim. The presence of electronic money, something that cannot be denied, due to the rapid advances in science and technology, the law in this position is forced to be able to adjust and meet the demands for progress in this millennial era which is all over the world digital fast and accurate, it is possible that currency can be left behind under certain conditions.